KAJIAN ILMIAH IKAN PELANGI Marosatherina ladigesi (Ahl 1936) FAUNA ENDEMIK SULAWESI - Renny Kurnia Hadiaty (Research Center for Biology-Indonesian Institute of Sciences, 2007)
Marosatherina ladigesi is one of the famous rainbow fish species from Sulawesi.This endemic fish species from Sulawesi is one of the Indonesian export commodity since more than 30 years ago.All of the export specimens come from the wild habitat.The anxiousness of the extinction of this species stated in the redlist of IUCN since 1994. Two field work of Maros Karst Project conducted in 2006, 2007 and an international expedition in 2007 showed the decreasing population of this species.The results of the three field trips showed the difficulties to get M. ladigesi in the streams.Taxonomical status and classification, coloration, sex dimorphism and distribution discussed.